2016
DOI: 10.1063/1.4962717
|View full text |Cite
|
Sign up to set email alerts
|

Short minority carrier lifetimes in highly nitrogen-doped 4H-SiC epilayers for suppression of the stacking fault formation in PiN diodes

Abstract: We investigated the dependency of minority carrier lifetimes on the nitrogen concentration, temperature, and the injected carrier concentration for highly nitrogen-doped 4H-SiC epilayers. The minority carrier lifetimes greatly shortened when the nitrogen concentration exceeded 1018 cm−3 through enhancing direct band-to-band and Auger recombination and showed a slight variation in the temperature range from room temperature (RT) to 250 °C. The epilayer with a nitrogen concentration of 9.3 × 1018 cm−3 exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…No difference has been observed in these samples regarding electrical, optical and structural properties, indicating that V concentration is probably similar in both samples and V has a strong memory effect. It has been suggested that, in order to avoid the penetration of bipolar plasma into the substrate and hence the formation of stacking faults in SiC-based PiN devices, V doping can be used in the buffer layer to effectively kill bipolar plasma 25 . V has also shown to effectively control charge carrier lifetime in 4H-SiC epilayers, when used at very low and controlled concentration (<1x10 13 cm -3 ) 26 .…”
Section: Optical Propertiesmentioning
confidence: 99%
“…No difference has been observed in these samples regarding electrical, optical and structural properties, indicating that V concentration is probably similar in both samples and V has a strong memory effect. It has been suggested that, in order to avoid the penetration of bipolar plasma into the substrate and hence the formation of stacking faults in SiC-based PiN devices, V doping can be used in the buffer layer to effectively kill bipolar plasma 25 . V has also shown to effectively control charge carrier lifetime in 4H-SiC epilayers, when used at very low and controlled concentration (<1x10 13 cm -3 ) 26 .…”
Section: Optical Propertiesmentioning
confidence: 99%
“…The 1SSFs of T1 and T3 had a right-angled corner on the right side, and these two types are the most frequently observed and repo rted. 3,[5][6][7][9][10][11][12][13][14]16,[19][20][21][22] However, the 1SSFs of T2 had a triangular shape with a right-and-left in contrast to T1 and T3. The expansion direction of T2, which was from the surface to the substrate/epilayer interface, was opposite to that of T3.…”
Section: Resultsmentioning
confidence: 93%
“…4 Most previous studies on the expansion of 1SSFs have found that the SSFs originate from two kinds of BPDs: one that had penetrated from the substrate into the epilayer, 5,6 and another that had converted to a threading edge dislocation (TED) around the substrate/epilayer interface during epitaxial growth. 7 In addition, many analyses have been conducted of these 1SSFs, including current/temperature stress testing, [8][9][10][11][12][13][14] calculations, [15][16][17][18] and crystal analysis. [19][20][21][22][23] The BPD detection by photoluminescence (PL) imaging and the use of a buffer layer between the substrate and the epitaxial layer was proposed as a method for controlling 1SSF expansion 4,7,11,24 with the aim of solving the V F degradation issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To suppress 1SSF expansion, proper design of the buffer layer, which is the first thin layer grown on a substrate, is important. Tawara et al have clearly demonstrated the relationship between the injected carrier concentration and 1SSF expansion, and showed that a recombination-enhancing buffer layer in p-i-n diodes suppresses 1SSF expansion 33 , 34 . However, a thick buffer layer is necessary to suppress 1SSF expansion under a high current density, resulting in an increased process cost.…”
Section: Introductionmentioning
confidence: 99%